PEMANFAATAN SISTEM INFORMASI MANAJEMEN SEBAGAI STRATEGI DALAM MENJALIN KERJASAMA SEKOLAH DENGAN WALI MURID DI SEKOLAH MENENGAH PERTAMA NEGERI 1 TALAMAU - Hanifa Zakia (Jurnal Bahana Manajemen Pendidikan, 2019)
Includes data management and data storage management is done simply where data is only stored in excel. It looks less effective and efficient in technology’s development. Now, in Education, the lack of good cooperation between the school and parents to support the application of management information systems to improve quality of education. This is the implementation of Management Information System is already being adopted by schools, especially in SMP N 1 Talamau. The researcher use field research method that is qualitative research. The outcomes are that existing management information systems already meet the standards, both in terms of the student, curriculum, human resources, the facilities and the quality of the user, who is able to manage the activities that exist in the school. And then, the role of parents is also important in implementing management information systems to improve the quality of education. SMP N 1 Talamau applies a specific strategy that utilizes information technology-based Management Information Systems, namely an information and consultation room that functions as a consultation center between the school and parents and gives access to parents to see the development of students' Academic values.